β-Dihydroagarofuran-type Sesquiterpenoids from the Stems of Celastrus orbiculatus with their Cytotoxic Activities - Hua Lin, Yong; Zhang, Bao Y.; Chen, Zhi Chao; Wei, Jian Feng (Letters in Organic Chemistry, 2022)
A new β-dihydroagarofuran-type sesquiterpenoid named 1α,2α,5α,11-tetraacetoxy-8α- (trans-p-coumaroyl)-β-dihydroagarofuran (1), together with five known compounds (2-6), was isolated from the CHCl3-soluble extract of the stems of Celastrus orbiculatus. The structure of the new compound was elucidated with spectroscopic physicochemical analyses. All isolates were evaluated for in vitro cytotoxic activity against four human cancer lines, including HepG2, MCF-7, A549, and HCT-116 cells. Among them, compounds 1 and 6 showed potent cytotoxic activities against HepG2 cells with IC50 values of 8.78 ± 2.31 and 10.28 ± 1.15 μM, respectively. In addition, compound 6 exhibited significant cytotoxic activity against HCT-116 cells with an IC50 value of 6.37 ± 2.52 μM.
Keywords: sesquiterpenoids